2022
DOI: 10.1038/s41380-022-01806-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways of major depressive disorder converge on the synapse

Abstract: Major depressive disorder (MDD) is a psychiatric disease of still poorly understood molecular etiology. Extensive studies at different molecular levels point to a high complexity of numerous interrelated pathways as the underpinnings of depression. Major systems under consideration include monoamines, stress, neurotrophins and neurogenesis, excitatory and inhibitory neurotransmission, mitochondrial dysfunction, (epi)genetics, inflammation, the opioid system, myelination, and the gut-brain axis, among others. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 250 publications
0
78
0
1
Order By: Relevance
“…Extensive studies at different molecular levels point to a high complexity of numerous interrelated pathways as the underpinnings of MDD and its highly heterogeneous symptomatology, including agitated depression with manifestations of excessive aggression [ 17 , 18 ]. Major systems under consideration include monoamines, the hormonal axis of stress response, neurotrophins, excitatory and inhibitory neurotransmission, mitochondrial dysfunction, epigenetics, inflammation, the opioid system, myelination and the gut–brain axis, among others [ 17 , 19 ]. Currently, a vast body of the latest literature points to new mechanisms for MDD and its associated symptoms, such as impulsivity and aggression.…”
Section: Major Depressive Disorder and Excessive Aggressionmentioning
confidence: 99%
“…Extensive studies at different molecular levels point to a high complexity of numerous interrelated pathways as the underpinnings of MDD and its highly heterogeneous symptomatology, including agitated depression with manifestations of excessive aggression [ 17 , 18 ]. Major systems under consideration include monoamines, the hormonal axis of stress response, neurotrophins, excitatory and inhibitory neurotransmission, mitochondrial dysfunction, epigenetics, inflammation, the opioid system, myelination and the gut–brain axis, among others [ 17 , 19 ]. Currently, a vast body of the latest literature points to new mechanisms for MDD and its associated symptoms, such as impulsivity and aggression.…”
Section: Major Depressive Disorder and Excessive Aggressionmentioning
confidence: 99%
“…Depression is a negative emotion, accompanied by thoughts of failure, hopelessness and even suicide, which is one of the most disabling psychiatric disorders, and has afflicted more than 300 million patients worldwide, especially in the course of the COVID-19 pandemic [ 1 – 3 ]. During the past few decades, numerous studies have shown that depression is a multifactorial disease, including but not limited to monoamines, inflammation, neurotrophies and neurogenesis, as well as (epi)genetics [ 4 ]. Among these, inflammatory depression, an emerging subtype of depression, has recently received extensive attention owing to the solid evidence of “inflammation hypothesis of depression” [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite poorly understood molecular and cellular mechanisms of depression, accumulated data indicate that the pathophysiology of this disease is associated with disturbances in closely interrelated nervous, immune, and neuroendocrine systems. These disruptions affect patterns of synaptic activity in the brain, which is reflected in changes in consciousness, behavior, mood, and emotions [ 363 ]. The complexity of the mechanisms that cause depression-associated states of the nervous system corresponds to the existence of several hypotheses of the causes of depression and the mechanisms of action of antidepressant drugs.…”
Section: Discussionmentioning
confidence: 99%